Sexual problems and personality traits in female patients with Fibromyalgia Syndrome without diagnosis of sexual dysfunction (Annals of Medical Research, 2021)
Aim: Fibromyalgia syndrome (FMS) is a disease characterized by generalized chronic pain accompanied by hypersensitivity in tender anatomic regions and by various psychiatric disorders. The aim of this study was comparing the relationships between FMS symptoms and the personal characteristics and sexual problems in patients.Materials and Methods: The study was conducted at a Dr.Sadi Konuk Training and Research Hospital, Physical Therapy and Rehabilitation Unit in Istanbul. The study included 24 female patients were diagnosed with FMS without presence of sexual dysfunction. The demographic and anthropometric characteristics, the symptoms accompanying FMS and tender points were identified. Visual Analog Scale (VAS), Fibromyalgia Impact Questionnaire (FIQ), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Minnesota Multiphasic Personality Inventory (MMPI) and Golombok Rust Inventory of Sexual Satisfaction (GRISS) were utilized. Results: From MMPI scores, only “hysteria” sub-item score was above 70 (µ=73.63). The mean “feel good”, “work missed” and “anxiety” subscale scores of FIQ had a statistically significant positive correlation with “vaginismus”, “touching”, “anorgasmia” subscale and “total” scale scores of GRISS. A statistically significant positive correlation was found between BDI and GRISS “communication” scores and between BAI and GRISS “touching” scores.Conclusion: We found an association between FMS complaints and some symptoms of sexual dysfunction. The high mean MMPI "hysteria" score of patients indicates that they use suppression and denial quite often and they may have somatic complaints associated with anxiety. BDI and BAI scores were found to be high and associated with some symptoms of sexual dysfunction in our study.
Keywords: Fibromyalgia Syndrome; sexual problems; personality traits